Silver Recovery from E-Waste Printed Circuit Board Using Binary and Ternary Deep Eutectic Solvents - Arrizal Abdul Aziz; Abraham Mora; Soja Siti Fatimah; Omay Sumarna; Hufaidatul Azfa Nurusyifa; Sheren Hana Elia; Ira Kamilia Siti Huwaidah (Jurnal Kimia Sains dan Aplikasi, 2024)
Printed Circuit Boards (PCBs) are essential components of electronic devices containing valuable silver metal. Using sustainable methods, silver recovery from electronic trash, like PCBs, demonstrates excellent promise. This research’s objective is to determine the optimum leaching time and solid-to-liquid (S/L) ratio for extracting silver from PCB using deep eutectic solvent (DES) composed of choline chloride and glycerol (glyceline DES). The binary DES’s leaching performance was then compared to choline chloride, glycerol, and citric acid ternary systems. Fourier Transform Infrared Spectroscopy (FTIR) was carried out to analyze the bond interactions. X-ray fluorescence spectrometry (XRF) was employed to determine the PCB’s metal concentration prior to and after the leaching process. Ternary DES was viscous, colorless, stable for 60 days, and less acidic than binary DES, with a 1.21 g/mL density. FTIR peak broadening and shifting indicated the formation of a new hydrogen bond and proved a successful synthesis of ternary DES. XRF result showed that PCB’s initial silver metal content was 2.32%. The optimal silver leaching from PCB using glyceline DES was achieved after 16 hours, with a 1/20 solid-to-liquid ratio. Ternary DES demonstrated a silver leaching efficiency of 93.65%, surpassing 86.77% of glyceline. Ternary DES synthesized in this study has the potential to serve as an efficient and environmentally friendly solvent for extracting silver from PCB, providing a sustainable approach to managing electronic waste.